Impact of vancomycin therapeutic drug monitoring on mortality in sepsis patients across different age groups: a propensity score-matched retrospective cohort study - Peng, Huaidong; Zhang, Ruichang; Zhou, Shuangwu; Xu, Tingting; Wang, Ruolun; Yang, Qilin; Zhong, Xunlong; Liu, Xiaorui (Frontiers in Medicine, 2024)
Background: Due to its potent antibacterial properties, vancomycin is frequently used in the treatment of sepsis. Therapeutic drug monitoring (TDM) can optimize personalized vancomycin dosing regimens, potentially enhancing therapeutic efficacy and reducing nephrotoxicity. However, it remains uncertain whether TDM affects the mortality rate among sepsis patients or whether age plays a role in this outcome.We analyzed data from the MIMIC-IV database of sepsis patients admitted to the intensive care unit (ICU) and treated with vancomycin. Our primary variable of interest was whether vancomycin TDM was conducted during the ICU stay. The main outcome was 30-day mortality. To adjust for confounders and assess associations, we used Cox proportional hazards regression and propensity score matching (PSM). Subgroup and sensitivity analyses were performed to test the robustness of our findings. Additionally, we employed restricted cubic spline models to investigate 2 the relationship between age and mortality among different groups of sepsis patients, aiming to identify potential non-linear associations.Results: A total of 14,053 sepsis patients met the study criteria, of whom 6,826 received at least one TDM during their ICU stay. Before PSM, the 30-day mortality rate was 27.2% (1,856/6,826) in the TDM group and 16.2% (1,494/7,227) in the non-TDM group. After PSM, analysis of 4,329 matched pairs revealed a significantly lower 30-day mortality in the TDM group (23.3%, 1,010/4,329) compared with the non-TDM group (27.7%, 1,201/4,329) (p < 0.001). Multivariable Cox proportional hazards regression showed a significantly reduced 30-day mortality risk in the TDM group (adjusted hazard ratio [HR]: 0.66; 95% confidence interval [CI]: 0.61-0.71; p < 0.001). This finding was supported by PSM-adjusted analysis (adjusted HR: 0.71; 95% CI: 0.66-0.77; p < 0.001) and inverse probability of treatment weighting (IPTW) analysis (adjusted HR: 0.72; 95% CI: 0.67-0.77; p < 0.001). Kaplan-Meier survival curves also indicated significantly higher 30-day survival in the TDM group (log-rank test, p < 0.0001). Vancomycin TDM is associated with reduced 30-day mortality in sepsis patients, particularly among those aged 18 to 50, who exhibited the lowest mortality rates and the greatest reduction following TDM compared with older patients.